Microlepidogaster arachas, a new species of hypoptopomatine catfish (Siluriformes: Loricariidae) from the upper rio Paraná basin, Brazil - Martins, Fernanda O.; Calegari, Bárbara B.; Langeani, Francisco (Zootaxa, 2013)
Microlepidogaster arachas Martins, Calegari & Langeani, sp. nov., a new Hypoptopomatinae, is described from the upper rio Paraná basin. The new species is distinguished from M. longicolla and M. dimorpha by having the anterior portion of the compound supraneural plus first dorsal-fin proximal radial contacting the neural spine of the ninth vertebra. The new species differs from M. perforatus by having 18–29 dentary teeth; median series of lateral plates complete, reaching caudal-peduncle end, and continuous lateral line; and 20–24 mid-dorsal plates. Microlepidogaster arachas is further distinguished from its congeners by several other osteological features.